2007
DOI: 10.1002/jmri.20957
|View full text |Cite
|
Sign up to set email alerts
|

Motion corrected free‐breathing delayed‐enhancement imaging of myocardial infarction using nonrigid registration

Abstract: Purpose:To develop and test an automatic free-breathing, delayed enhancement imaging method with improved image signal-to-noise ratio (SNR). Materials and Methods:The proposed approach uses freebreathing, inversion-recovery single-shot fast imaging with steady precession (FISP) delayed-enhancement with respiratory motion compensation based on nonrigid image registration. Motion-corrected averaging is used to enhance SNR.Results: Fully automatic, nonrigid registration was compared to previously validated rigid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 23 publications
(32 reference statements)
0
80
0
Order By: Relevance
“…This has been applied to delayed enhanced cardiac MRI, 79 as well as to wholeheart coronary MRA 80 to our knowledge.…”
Section: -72mentioning
confidence: 99%
“…This has been applied to delayed enhanced cardiac MRI, 79 as well as to wholeheart coronary MRA 80 to our knowledge.…”
Section: -72mentioning
confidence: 99%
“…Using a model that incorporates regional scar thickness to estimate VT excitation wavefront propagation, the VT circuit isthmus was predicted and shown to overlap the actual isthmus, observed by electrical mapping, by around 90%. Although these experimental studies use signifi cantly higher-resolution DEMRI maps than what is currently acquired clinically, methods to obtain higher-resolution scar images in patients are being developed [32]. Together with studies to identify safe MRI protocols for patients with implanted defi brillators [33] and clinical correlation of DEMRI scar morphology to successful VT ablation sites, the role of MRI for clinical VT ablation will be better defi ned.…”
Section: Delayed-enhancement Mri For Vt Ablation Planningmentioning
confidence: 98%
“…A similar approach has also been validated for ECG-triggered, free-breathing DE-MR imaging during a single cardiac phase. 29,30 Another tactic is to use a respiratory-triggered, segmented SSFP sequence, which eliminates the breath-hold requirement in cine SSFP and has been validated in healthy volunteers and sedated children. 31 A recent study in adult patients showed that the LV functional values obtained with this respiratory-triggered free-breathing SSFP technique are in good agreement with the results obtained with a breath-hold SSFP sequence (Fig.…”
Section: Free-breathing Cine Techniquesmentioning
confidence: 99%